Fetus in the Abdominal Cavity After Uterine Rupture in a Primigravida Post-Adenomyosis Enucleation - Saki Kamata; Hanano Ando; Erina Matsuda; Aiko Aoki; Atsushi Komatsu; Kei Kawana (Diagnostics)
A 35-year-old primigravida with a history of adenomyosis enucleation was diagnosed with abnormal fetal position at 25 weeks of gestation. The patient presented with normal vital signs and no symptoms. A cardiotocogram and transabdominal ultrasound revealed a healthy fetus, normal amniotic fluid volume, and no intra-abdominal bleeding. Pelvic magnetic resonance imaging (MRI) indicated a ruptured muscular layer of the uterine fundus, with the fetus completely prolapsed into the abdominal cavity. An emergency cesarean section was performed, during which the fetus was found wrapped within the amniotic membrane in the abdominal cavity. The uterus exhibited extensive tearing along the line of the previous surgical scar; however, no hemorrhage was observed. In this case, despite uterine rupture, blood flow through the umbilical cord from the placenta in the uterus resulted in the survival of the fetus. In addition, MRI was essential in determining the appropriate timing to save the fetus.